2022
DOI: 10.3390/ma15134446
|View full text |Cite
|
Sign up to set email alerts
|

Structural Strength Analyses for Low Brass Filler Biomaterial with Anti-Trauma Effects in Articular Cartilage Scaffold Design

Abstract: The existing harder biomaterial does not protect the tissue cells with blunt-force trauma effects, making it a poor choice for the articular cartilage scaffold design. Despite the traditional mechanical strengths, this study aims to discover alternative structural strengths for the scaffold supports. The metallic filler polymer reinforced method was used to fabricate the test specimen, either low brass (Cu80Zn20) or titanium dioxide filler, with composition weight percentages (wt.%) of 0, 2, 5, 15, and 30 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Recently, our X-ray diffraction (XRD) tests [ 74 ] for CuZn powder found that the results were coincidently similar to those of Nogueira et al (2022) [ 75 ], as shown on the left of Figure 2 with the blue colour lines and black colour dots, respectively. The XRD test found two main peaks at two similar diffraction angles of 2θ degrees, indicating the CuZn and Cu 5 Zn 8 phases.…”
Section: Other Stimuli and Chemotherapiessupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, our X-ray diffraction (XRD) tests [ 74 ] for CuZn powder found that the results were coincidently similar to those of Nogueira et al (2022) [ 75 ], as shown on the left of Figure 2 with the blue colour lines and black colour dots, respectively. The XRD test found two main peaks at two similar diffraction angles of 2θ degrees, indicating the CuZn and Cu 5 Zn 8 phases.…”
Section: Other Stimuli and Chemotherapiessupporting
confidence: 86%
“… XRD intensity against diffraction angle of 2θ for CuZn (left) [ 74 , 75 ] and illustration of Cu-bonded polyester urethane via N (right) [ 54 ]. Reprinted with permission.…”
Section: Figurementioning
confidence: 99%
“…Scientists and clinicians have attempted to solve these problems for the past thirty years [20], but 30% of OS patients still do not respond to these standard treatments [21]. Therefore, combinational and targeted therapies [22] [23] are developed for these problems and has a higher response rate [24]. However, their evidence of efficacy, long-term use [25], and personalised precision medicine [26] remain inadequate [27].…”
Section: Of 26mentioning
confidence: 99%
“…Extensive research on the mechanical and microstructural properties of widely used cast, wrought, or hot-forged CoCrMo alloys has been reported [ 6 , 12 , 13 , 14 , 15 ]. To fulfill the criteria for metallic materials as feasible implants, it is important to reduce the stress shielding effect and enhance osseointegration [ 16 , 17 , 18 , 19 , 20 , 21 ] by applying porous lattice structures, which are difficult to achieve via traditional fabrication processes.…”
Section: Introductionmentioning
confidence: 99%